REMOTE SENSING RESEARCH: A User's Perspective - Sutanto Sutanto (Faculty of Geography, Universitas Gadjah Mada, 2010)
Remote sensing technology has been adopted by various fields of sciencesince the Second World War. Its research varies greatly accordingly. Basically itcan be broken down into there types,i.e, (1)research using remote sensing just fordata acquisition, (2) research in theoretical remote sensing, and (3) research inapplied remote sensing. This article is about its differentiation.